Structural Analysis of Ginsenosides and Sugars: An Electrospray and Tandem Mass Spectrometry Study - Ackloo, Suzanne (My University, 2001)
Carbohydrates are an abundant class of biological molecules. This thesis presents methodologies for structure characterization of a class of triterpene glycosides, the ginsenosides, sugars and polyols. The sugars included simple monosaccharides, as well as complex saccharides such as the carrageenans, a family of sulfated polysaccharides. The methodologies employed positive and negative ion electrospray ionization (ESI) mass spectrometry and tandem mass spectrometry (MS/MS).
Positive ion electrospray mass spectrometry (ESMS) of solutions containing a ginsenoside and any alkali metal ion produced the [M+metal]+ ion. By contrast, when the transition metal ions, Ni++, Co++ and Zn++, are used, the [M+Metal-H]+ ion was observed. Collision-induced dissociation (CID) of the metal attachment ions accommodated their structure characterization. The relative intensity ratio of the product ions provided information on the point of attachment of the sugars to the core, as well as whether they are monosaccharides or disaccharides.
Negative ion ESMS of basic solutions of ginsenosides showed a peak corresponding to the [M-H]- ion whose CID spectrum provided the identity of the core, the sugars comprised in the ginsenoside and their order of attachment to the ginsenoside. Both positive and negative ion CID experiments provided information that can be used to propose a structure for ginsenosides. In line with this, these methodologies were used to develop a liquid chromatography mass spectrometry (LC/MS) and LC/MS/MS method for separation and structural characterization of new ginsenosides from root extracts. The structure proposals for ten new ginsenosides are provided.
The carrageenans are a family of partially sulfated polysaccharides of which there are three major types, kappa (k), iota (i) and lamda (l). These types are different because each has a disaccharide subunit containing a specific number of sulfate groups with Na+ counterions. Both matrix-assisted laser/desorption ionization time-of-flight mass spectrometry and negative ion ESMS proved to be useful structure probes for these compounds. Dilute solutions of carrageenans undergo H+ exchange and subsequent expulsion of SO3 thus generating a carrageenan with lower sulfate content.
Ginsenosides differing only in the presence of geometric isomeric sugars are not differentiated by CID experiments. This observation raised the question of differentiating geometric and (stereo) isomeric polyols using ESMS and MS/MS experiments. Two approaches were investigated to address this question; the first employing negative ion, and the other positive ion mode.
The structures of polyols and sugars were analyzed as their boric acid complexes by negative ion infusion ESMS and MS/MS experiments. The positive ion approach employed complexation to oxovanadium(IV), VO++. In both systems, ethylene glycol the simplest polyol was employed as the internal standard. Full scan ESMS experiments provided information on the ease of complexation of the analyte relative to ethylene glycol by comparing the intensity ratio of ions corresponding to their complexes with boric acid and VO++. CID experiments probed the structures of these complexes. Both methodologies were valuable for differentiating geometric and stereoisomeric diols, and isomeric methyl glycosides.
Both ESI and MALDI involve solution- and gas-phase processes. A small chemical ionization mass spectrometry project involving alkylation reactions of N-ethyl- and N-methylaniline, and o-, m- and p-ethyl- and o-, m- and p-methylaniline with iodomethane and iodoethane was undertaken. It was observed that the N-site is the primary site for alkylation.
Keywords: Chemistry; Chemistry